Maternal and Foetal Cellular Immune Responses in Dams Infected With High- and Low- Virulence Isolates of Neospora caninum at Mid-Gestation - García-Sánchez, Marta; Jiménez-Pelayo, Laura; Vázquez, Patricia; Horcajo, Pilar; Regidor-Cerrillo, Javier; Jiménez-Meléndez, Alejandro; Osoro, Koldo; Ortega-Mora, Luis Miguel; Collantes-Fernández, Esther (Frontiers in Cellular and Infection Microbiology, 2021)
Bovine neosporosis is currently considered one of the main causes of abortion in cattle worldwide and the outcome of the infection is, in part, determined by Neospora caninum isolate virulence. However, the dam and foetal immune responses associated with this factor are largely unknown. We used a model of bovine infection at day 110 of gestation to study the early infection dynamics (10- and 20-days post-infection, dpi) after experimental challenge with high- and low-virulence isolates (Nc-Spain7 and Nc-Spain1H, respectively). In the present work, dam peripheral cellular immune responses were monitored twice a week from -1 to 20 dpi. At different time points, IFN-γ and IL-4 production was investigated in stimulated dam blood and the percentage of monocytes, NK cells, B cells and T cells (CD4+, CD8+ and γδ) in peripheral blood mononuclear cells (PBMC) were determined by flow cytometry. In addition, maternal iliofemoral lymph nodes and foetal spleen and thymus were collected at 10 and 20 dpi for the study of the same cell subpopulations. Peripheral immune response dynamics were similar after the infection with both isolates, with a significant increase in the percentage of CD4+ T cells at 6 and 9 dpi in PBMC, coincident with the higher levels of IFN-γ and IL-4 release. However, the levels of IFN-γ were significantly higher and an increase in CD8+ T cells at 9, 13 and 20 dpi was observed in the dams infected with Nc-Spain7. Nc-Spain1H infection induced higher IL4 levels in stimulated blood and a higher CD4+/CD8+ ratio in PBMC. The analysis of the maternal iliofemoral lymph node showed a significant enhancement in the percentage of NK, CD4+ and CD8+ T cells for the animals infected with the highly virulent isolate and euthanized at 20 dpi. Regarding the foetal responses, the most remarkable result was an increase in the percentage of monocytes at 10 dpi in the spleen of foetuses from both infected groups, which suggests that foetuses were able to respond to N. caninum infection at mid gestation. This work provides insights into how isolate virulence affects the maternal and foetal immune responses generated against N. caninum.